INTERPRERASI A CONTRARIO TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 30/PUU-XVI/2018 TENTANG LARANGAN PENGURUS PARTAI POLITIK MENJADI ANGGOTA DPD - Aulia Rasyid Sabu; Mexsasai Indra; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Decision of the Constitutional Court against the management of political parties against being a Member of the Regional Representative Council of the Republic of Indonesia (DPD RI). A studio review of the Mahmakah constitution No. 30 / PUU-XVI / 2018 which is more focused on the requirements of DPD members governing Article 182 Letter l of Law Number 7 of 2017 Concerning General Elections, the Basic Law makes this decision questionable on the principle of negativity legislator Article 12 paragraphs (1) and (3) of the 1945 Constitution which regulates rights and obligations in the country, namely the 1945 Constitution which provides rights and obligations for countries participating in using democracy in Indonesia. The Constitutional Court approved the constitutional articles but examined that this was done to protect the integrity of Human Rights, not to demand Human Rights approved by the constitution, to question the Constitutional Court which is called the the guardian of the constitution. This type of research can be classified in normative juridical research, because this research was conducted by examining secondary data and approaches to the law, this normative study examines the principles of law. Sources of data used are primary data, secondary data, tertiary data, data collection techniques in this study are normative juridical, the data used is literature study. The results of the research conducted by the author are that the Constitutional Court in deciding a case is often out of the authority granted by the Act, resulting in the absence of legal certainty considering the decision of the Constitutional Court is final and binding. The Constitutional Court in making a decision Number 30 / PUU-XVI / 2018 is not perfect because it causes legal uncertainty in Indonesian law, and the Constitutional Court has restricted the rights of Indonesian citizens. Therefore, when the Constitutional Court makes a ruling it should not contradict the Basic Law so that legal certainty is guaranteed for Indonesian citizens and the Constitutional Court does not limit the rights of its citizens to participate in organizing democracy.Keywords: Constitutional Court Decisions – Members of Political Parties - Political Rights